A changing role? Educational psychologists in South Africa: two decades beyond democracy - Kumar, Pragashni Asim (My University, 2017)
The study aimed to explore the views of practicing educational psychologists on their roles and functions within the South African context. The main purpose of the study was to document demographic and descriptive data in relation to educational psychologists’ training, areas of work, and views of their roles and functions, within the context of changes in education policy and their professional practice in South Africa. The study used a descriptive survey design. One hundred and twenty seven respondents who were qualified educational psychologists completed a self- designed descriptive questionnaire. The findings of this study indicate that majority of educational psychologists in South Africa are practicing in a private practice capacity and majority service urban areas. Educational psychologists in this study highlighted three key areas of psychological intervention that they are engaged in, namely psycho-educational assessments, parent guidance, and child psychotherapy. Other key findings in this report highlight the gaps in training experienced by the respondents; the positive and negative aspects of the Education White Paper 6 policy as experienced by the respondents and their views on the educational psychology scope of practice.
A research report submitted to the Discipline of Psychology in the School of Human and Community Development in partial fulfilment of the requirements for the degree of Master in Education (Educational Psychology) in the faculty of Humanities, University of the Witwatersrand, Johannesburg 2017
Keywords: Educational psychology--South Africa; Child psychotherapy--South Africa